Erratum to "New discoveries and interpretations of hominid fossils and artifacts from Vindija Cave, Croatia" (J. Hum. Evol.46 (1) (2004) 27 - 67) - Ahern, James (Array, 2005)
The authors regret that the Vindija Cave fossil specimen Vi 13.10 was misidentified as a hominid scapular fragment. Upon further analysis, it is clear that this specimen is most likely a fragment of carnivore ilium.